PENGEMBANGAN KEMAMPUAN BERBAHASA LISAN MELALUI METODE BERCERITA DENGAN MEDIA BONEKA TANGAN KELOMPOK USIA 4-5 TAHUN - Nurkhasyanah, Alfiyanti; Hartiningsing, Nining; Rahayu, Eka Pamuji; Rohyana, Hadi (Jurnal Anak Bangsa, 2024)
This research aims to develop oral language skills through the storytelling method using hand puppets in the 4–5-year age group. The type of research used in this research is collaborative classroom action research using the Kemmis and Mc Taggart research model. The research subjects were 17 children from the TK An Islam TK IT Abata Lombok group. Data collection techniques include observation and documentation. The research instrument used was an observation sheet instrument in the form of a checklist. Data analysis was carried out through quantitative and qualitative descriptive methods. The indicator of success in this research is if the child's oral language ability reaches 82% and gets 4 stars. The results of the research show that oral language ability through the storytelling method using hand puppets has increased. This can be seen from the proportion of children who received a very good category score, namely Very Well Developed or BSB, in cycle I increased by 23.5% and in cycle II increased by 82.3%. This shows that the use of hand puppet media, especially in TK IT Abata Lombok I, has proven to be more effective in improving the oral language skills of children aged 4-5 years